Thermal system design and simulation - Dhar, P. L. (Academic Press, 2017)
Thermal System Design and Simulation covers the fundamental analyses of thermal energy systems that enable users to effectively formulate their own simulation and optimal design procedures. This reference provides thorough guidance on how to formulate optimal design constraints and develop strategies to solve them with minimal computational effort. The book uniquely illustrates the methodology of combining information flow diagrams to simplify system simulation procedures needed in optimal design. It also includes a comprehensive presentation on dynamics of thermal systems and the control systems needed to ensure safe operation at varying loads. Designed to give readers the skills to develop their own customized software for simulating and designing thermal systems, this book is relevant for anyone interested in obtaining an advanced knowledge of thermal system analysis and design.--Provided by publisher.